POLYMERS IN VACCINE FORMULATION - Mustafaeva, Zeynep (YILDIZ TECHNICAL UNIV, 2016)
Synthetic peptides that bind to carrier polymer molecules to use recent vaccine technology can create a higher immune response, remain longer in biological systems and they may be more stable against degrading. This is why synthetic peptides are given to living systems either by creating a microatmosphere or a conjugate. In these systems where natural or synthetic polymers can be used; synthetic carriers have more advantage compared to natural carriers such as obtainingproducts with high purity yields, manipulating structure and the molecular weight as desired, creating specific effects with simple additions of various chemical groups to the structure. In this study, linear and spherical polymeric carrier were examined for synthetic peptide, several examples are given to polymeric carrier and examined immune response and their advantage.
Keywords: Polymeric carriers; polyelectrolytes; nanoparticles; DELIVERY; Engineering